2014
DOI: 10.1080/08927014.2014.904294
|View full text |Cite
|
Sign up to set email alerts
|

The ability of an antimicrobial agent to penetrate a biofilm is not correlated with its killing or removal efficiency

Abstract: The penetration ability of 12 antimicrobial agents, including antibiotics and biocides, was determined against biofilms of B. cereus and P. fluorescens using a colony biofilm assay. The surfactants benzalkonium chloride (BAC) and cetyltrimethyl ammonium bromide (CTAB), and the antibiotics ciprofloxacin and streptomycin were of interest due to their distinct activities. Erythromycin and CTAB were retarded by the presence of biofilms, whereas ciprofloxacin and BAC were not. The removal and killing efficacies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 70 publications
(92 reference statements)
0
21
0
Order By: Relevance
“…The ability of an antibiotic agent to penetrate a biofilm may not tell us anything about its efficacy (33), but penetration of the biofilm seems to be important for effective antimicrobials so that all cells are exposed to the antimicrobial agent.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of an antibiotic agent to penetrate a biofilm may not tell us anything about its efficacy (33), but penetration of the biofilm seems to be important for effective antimicrobials so that all cells are exposed to the antimicrobial agent.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the bacteria in the dual species biofilms had higher resistance to killing but a decreased resistance to removal, compared with the single species biofilms, particularly those formed by P. fluorescens. In fact, the killing and the removal of a biofilm are distinct processes (Araújo et al, 2014;Chen and Stewart, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…membrane resulting in release of intracellular constituents (Trueba et al, 2013). QACs are positively charged big molecules, having strong affinity to protein and lipids which lead to difficulty in diffusion through the matrix before reaching the deep biofilm layers (Smirnova et al, 2010).Previous reports showed that biofilmicidal efficacy on B. cereus caused by QACs were ~50% and their ability to remove biofilm were around 15% as penetration of biofilm is not necessarily accompanied with killing the embedded cells (Araújo et al, 2014). Beauchamp et al (2012) reported that quaternary ammonium chloride compounds were the least effective together with hypochlorite against E. coli O157:H7 biofilm cells, regardless of biofilm age, sanitizer concentration or exposure time however potas sium peroxymonosulfate have had better efficacy CONCLUSIONS C. jejuni biofilms buildup in poultry environment at different degrees regardless to time elapsed, biofilm on concrete was higher than galvanized wire and that of plastic.C.…”
Section: Resultsmentioning
confidence: 99%